Carbamato de etila em bebidas alcoólicas destiladas - Santos, Júlia Teresa [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Ethyl carbamate (EC) is a chemical contaminant in fermented foods and beverages such as bread, yogurt, wine, beer, as well as distilled beverages like whiskey and cachaça. It is proved by laboratory tests to be a carcinogen for animals, though it is considered a probable human carcinogen. In 2005, the Joint FAO/WHO Expert Committee on Food Additives (JECFA) assessed the risks involved with ethyl carbamate, and concluded that the combined intake of the contaminant from the daily diet and from alcoholic beverages is of concern, therefore recommends studies aiming the compound decrease in alcoholic beverages. This literature reviews aims to gather data on ethyl carbamate content in distilled alcoholic beverages from 2010 to 2015. Thirty-two articles from the electronic databases Web of Science, Science Direct, Scopus and PubMed were selected. Understanding EC formation is the first step in studying prevention and/or elimination methods. Most of the contaminant is formed after distillation by reaction of ethanol with cyanate and its derivatives (isocyanate, cyanic acid and isocyanic acid). Other factors, such as the presence of copper, heat, aging, storage in the presence of light, favor formation. The official method of analysis of EC for alcoholic beverages is based on Gas chromatography-mass spectrometry (GC/MS), but another method that is gaining space for its speed and sensitivity is High-performance liquid chromatography with fluorescence detection (HPLC-FLD). Contaminant prevention and mitigation proposals have been extensively studied and implemented, ranging from simple methods to techniques involving genetic engineering, which in line with good manufacturing practices lead to effective control of EC. Most of the studies analyzed cachaças and sugarcane spirits. The higher EC levels were...

O carbamato de etila (CE) é um contaminante químico presente em alimentos fermentados, como pão, iogurte, vinho, cerveja assim como em bebidas destiladas, como uísque e cachaça. É reconhecido como carcinógeno em testes laboratoriais envolvendo animais, por isso é considerado um provável carcinógeno para humanos. Em 2005, o Comitê de Peritos em Aditivos Alimentares (JECFA) da Organização das Nações Unidas para Alimentação e Agricultura (FAO) e da Organização Mundial da Saúde (OMS) avaliou os riscos envolvidos com o carbamato de etila, e concluiu que a ingestão do contaminante da alimentação diária e de bebidas alcoólicas, combinadas, é motivo de preocupação, portanto recomenda estudos visando à diminuição deste composto em bebidas alcoólicas. Esse trabalho de revisão bibliográfica tem como objetivo reunir dados relativos à concentração do carbamato de etila encontradas em bebidas alcoólicas destiladas entre 2010 e 2015. Foram selecionados 32 artigos, obtidos dos bancos de dados eletrônicas Web of Science, Science Direct, Scopus e PubMed. Entender a formação do carbamato de etila é o primeiro passo para se estudar métodos de prevenção e/ou eliminação. A maior parte do contaminante é formada após a destilação, por reação do etanol com o cianato e seus derivados (isocianato, ácido ciânico e ácido isociânico). Outros fatores, como a presença de cobre, calor, envelhecimento, armazenamento na presença de luz, favorecem sua formação. O método oficial de análise de carbamato de etila para bebidas alcoólicas é baseado na cromatografia gasosa acoplada à espectrometria de massas (GC/MS), porém outro método que vêm ganhando espaço pela sua rapidez e sensibilidade é a cromatografia líquida de alta eficiência com detector...
Keywords: Bebidas destiladas; Bebidas alcoólicas; Carcinogenos; Cachaça